1998
DOI: 10.1002/(sici)1521-4176(199803)49:3<180::aid-maco180>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, diffusion and cluster formation at metal-polymer interfaces

Abstract: This paper shows how structure and formation of metal‐polymer interfaces depend strongly on the preparation process and the interfacial chemistry. Emphasis is placed on results obtained from transmission electron microscopy (TEM), X‐ray photo electron spectroscopy (XPS), radiotracer measurements and computer simulations on the early stages of interface formation during noble‐metal deposition onto fully cured polymers. Noble metal atoms deposited onto polymers diffuse on and inside the polymer and tend to agglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…In order for the penetration of the particles into the nylon 11 film to be energetically favorable, the Gibbs free energy of a metal particle must be lower than that of the isolated particle at the nylon 11 surface. If the surface tension of the particle γ particle exceeds the sum of the interfacial tension γ particle−nylon and the surface tension of the nylon 11 γ nylon , embedding of the metal particle is energetically favorable [22,23], γ particle > γ particle−nylon + γ nylon (1) i.e., nylon 11 matrix can wet completely the surface of the particles. In the previous work, we have shown that the inequality (1) is obeyed for the Au/nylon 11 system [19].…”
Section: Resultsmentioning
confidence: 99%
“…In order for the penetration of the particles into the nylon 11 film to be energetically favorable, the Gibbs free energy of a metal particle must be lower than that of the isolated particle at the nylon 11 surface. If the surface tension of the particle γ particle exceeds the sum of the interfacial tension γ particle−nylon and the surface tension of the nylon 11 γ nylon , embedding of the metal particle is energetically favorable [22,23], γ particle > γ particle−nylon + γ nylon (1) i.e., nylon 11 matrix can wet completely the surface of the particles. In the previous work, we have shown that the inequality (1) is obeyed for the Au/nylon 11 system [19].…”
Section: Resultsmentioning
confidence: 99%
“…20 Higher energy values are reported to improve metal deposition and stability on PDMS surfaces, but no accurate values have been published. 15 Instead, for other polymers, such as poly(acrylonitrile butadiene styrene), the surface energy is increased after Ar-plasma treatment from σ s = 40 to 75 mN/m, which doubled the adhesion strength of a sputtered Cu-layer. 29 With σ s = 40 mN/m, the adhesive strength of 8 MPa is already quite high for nonactivated polymer surfaces and could be a surface energy value for sufficient PDMS metallization.…”
Section: Discussionmentioning
confidence: 99%
“…This process is enhanced by the highly mobile macromolecular chains of the PDMS gel and increased temperatures due to the deposition process. 14,15 To avoid the undesired diffusion, many different activation processes like O 2 -plasma, [16][17][18] photochemically produced ozone (UV/ozone), [19][20][21] corona discharges 22 or the plasma polymerization of tetraethyl orthosilicate 23 and hexamethyldisiloxane 24 monomers are already known. These methods increase the surface energy and functionality of the PDMS surface and form a hard organoceramic layer as interface between the polymer and the metal layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To extract residual toluene, the film is annealed at about 10 ÿ6 mbar for 12 h at 30 K above the glass transition temperature of the bulk polymer (T G ) and then cooled down to 300 K at a slow rate of about 20 K=h. The gold clusters are produced in a high vacuum chamber by thermal evaporation of gold from a molybdenum crucible onto the polymer surface with a deposition rate of about 0:5 A= min, while the polymer surface is held at room temperature, leading to the confinement of the clusters in a narrow surface region [9]. The metal-metal interaction being much stronger than the metal-polymer one, the gold atoms diffuse on the polymer surface during the evaporation until they nucleate or eventually desorb again [10].…”
mentioning
confidence: 99%